2001
DOI: 10.1063/1.1402966
|View full text |Cite
|
Sign up to set email alerts
|

Selective etching of GaN polar surface in potassium hydroxide solution studied by x-ray photoelectron spectroscopy

Abstract: Etching characteristics of nondoped GaN films with the polar surface in KOH solution have been investigated. It is confirmed that the continuous etching in KOH solution takes place only for the GaN films with N-face (Ϫc) polarity independent of the deposition method and growth condition. It is found by x-ray photoelectron spectroscopy ͑XPS͒ analysis for the Ga face (ϩc) and N-face (Ϫc) GaN films that the atomic composition of the ϩc surface is not changed before and after dipping in KOH solution and that on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
252
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(287 citation statements)
references
References 23 publications
34
252
0
1
Order By: Relevance
“…As observed in Figure 2(c), the energy peak for N1s is centred at 397.3 eV, instead of 399 eV (binding energy of N element existing as atomic style), similar to the results of Li (397.4 eV) [17] and Veal (397.6 eV) [18], i.e. the N atom exists as a nitride.…”
Section: Methodssupporting
confidence: 65%
“…As observed in Figure 2(c), the energy peak for N1s is centred at 397.3 eV, instead of 399 eV (binding energy of N element existing as atomic style), similar to the results of Li (397.4 eV) [17] and Veal (397.6 eV) [18], i.e. the N atom exists as a nitride.…”
Section: Methodssupporting
confidence: 65%
“…2(d)] obtained for GaN grown at 450 C was fitted similarly using two subpeaks located at 397.49 and 395.67 eV, corresponding to N-Ga and Auger Ga bonds, respectively. 12,16 As the deposition temperature increases, the Ga 3d and N 1s binding energies (BEs) shifted from lower BE to the higher BE. The shift in the Ga 3d and N 1s core levels was observed to be 1 eV.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the Ga plane remains inert in aqueous KOH treatment but that the surface chemistry is affected, leading to a potential change in the band bending. 15 KOH treatment also results in a smooth surface. A large area Ohmic contact was formed on the substrate ͑N face͒ by electron beam evaporated Ti/ Al/ Pt/ Au ͑3 / 50/ 30/ 200 nm͒ to complete the fabrication of the vertical geometry diodes.…”
mentioning
confidence: 98%